Historical dictionary of Latvia - Purs, Aldis; Plakans, Andrejs (Historical dictionaries of Europe., 2017)
"Contains a chronology, an introduction, a bibliography, and a dictionary section with more than 500 cross-referenced entries on aspects of Latvia."--Provided by publisher